An ancient disease in a modern world - Walsh, Mary C. (Poligrafi, 2023)
For thousands of years people have attempted to understand epilepsy. Thro-ughout our long history, healing traditions have incorporated dreams into both epilepsy diagnosis and treatment. recent studies provide new information on the impact of epilepsy on sleep and dreaming, while research into epileptic dream content offers insight into the emotional and spiritual experience of people with epilepsy. Modern neurological research has increased our knowledge and improved treatment of this ancient disease, yet the stigma and misconceptions that have per-colated for millennia continue to impact epileptic care and quality of life globally. While modern technologies afford better treatment, they can also impact sleep, dreaming, and seizure frequency in epileptics. This article provides an overview of current research into dreams and epilepsy and explores implications of this research for epileptic care in a modern world. research surveyed includes recent stu-dies into the protective role of rEM sleep on seizures, epileptic dream content, the impact of epilepsy on specific populations and emerging paradigms for under-standing epileptic spiritual experience. Studies suggest the need for a multi-disci-plinary and multi-cultural approach to epilepsy. Implications for therapeutic and medical care, and avenues for future research are discussed.
Keywords: dreams; duhovnost; epilepsija; epilepsy; sanje; sleep; spanje; spirituality; technology; tehnologija